The Peruvian regulation of the deadline’s regime in PPP: considerations for its structuring and economic-financial implications of its breakdown - Salazar Carpio, Renzo Orlando (2025)
This academic paper analyzes and underscores the importance of regulating the temporal element in contracts entered into for the execution of public-private partnership (PPP) projects. It further seeks to explain how this element is often shaped by extra-legal factors, emphasizing that the timeframes established for the duration of such collaborative contracts –and for their specific execution deadlines– must be grounded in reasonable and objective justifications. This is essential to prevent arbitrary practices in their definition and, above all, to avoid unintended consequences for the management of public infrastructure and its private financing.To this end, the author examines how this matter is regulated under Peruvian law, explores the underlying premises supporting the need to regulate time-related provisions in such public contracts, and finally describes the economic and financial implications that may arise when disruptions or distortions occur in the temporal structure of PPP arrangements.